2013
DOI: 10.1002/14651858.cd004907.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Package of care for active management in labour for reducing caesarean section rates in low-risk women

Abstract: Background-Approximately 15% of women have caesarean sections (CS) and while the rate varies, the number is increasing in many countries. This is of concern because higher CS rates do not confer additional health gain but may adversely affect maternal health and have implications for future pregnancies. Active management of labour has been proposed as a means of reducing CS rates. This refers to a package of care including strict diagnosis of labour, routine amniotomy, oxytocin for slow progress and one to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
2
31
0
3
Order By: Relevance
“…Another Cochrane meta-analysis [7] examined only complete active management of labor packages and found results very close to those of the preceding meta-analysis. It used 7 of the 14 studies included in [6] above and found a modest but not significant reduction in the number of cesareans in the active management group (n=5390, RR 0.88, 95% CI 0.77-1.01) [7] (LE2).…”
Section: Page 6 Of 42supporting
confidence: 61%
See 2 more Smart Citations
“…Another Cochrane meta-analysis [7] examined only complete active management of labor packages and found results very close to those of the preceding meta-analysis. It used 7 of the 14 studies included in [6] above and found a modest but not significant reduction in the number of cesareans in the active management group (n=5390, RR 0.88, 95% CI 0.77-1.01) [7] (LE2).…”
Section: Page 6 Of 42supporting
confidence: 61%
“…A c c e p t e d M a n u s c r i p t 6 6 We identified four meta-analyses grouping together randomized or quasi-randomized trials published between 1998 and 2013 on this topic [5][6][7][8]. The first meta-analysis focused on the combined effects of an early amniotomy and early prescription of oxytocin on the risk of cesareans in nulliparas.…”
Section: Page 6 Of 42mentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, Paranjothy, Dowswell, and Thomas (2008), in their systematic review evaluating active management for reducing cesarean in low-risk women, found a modest decrease in the cesarean rate among the women who received amniotomy and oxytocin if their labors were delayed. A more recent Cochrane review (Wei et al, 2013) of the active management of labor included 14 trials and 8,033 women, and, again, this review showed ventions for when they are medically indicated has the potential to improve outcomes and make labor and birth safer and healthier for mothers and babies.…”
Section: Episiotomymentioning
confidence: 99%
“…Research has been conducted on how to prevent dystocia and facilitate vaginal delivery, involving active management of labour [22] and one-to-one care in labour [23]. Although the results have not shown a significant reduction of the CD rate, many birth wards base their procedures for ensuring progress in labour on active management of labour research.…”
Section: Introductionmentioning
confidence: 99%